PERTUMBUHAN DAN PERKEMBANGAN NODUS KENTANG (Solanum tuberosum L.) AKIBAT MODIFIKASI KONSENTRASI SUKROSA DAN PENAMBAHAN 2-ISOPENTENILADENINA SECARA IN VITRO - Asma Ul Husna; Luthfi Aziz Mahmud Siregar; Yusuf Husni (Universitas Sumatera Utara, 2014)
Potato is horticulture crops that able to consume its corm and used as food materials until a raw material toindustry in Indonesia . However, potato production capacity is not proportional to the increase in demand forpotatoes this time, one of this problem due to lack of availability of quality seed. In vitro tecniques is oneway that can be taken by using nodes as seed. Sucrose and cytokinin have an important part on it wheresucrose acts as a carbon source and energy while cytokinin is important in cell division to support a nodesgrowth. The research aimed to get a suitable concentration of sucrose and 2-isopenteniladenine (2-ip) forgrowth of number of potato (Solanum tuberosum L.) nodes by using in vitro methode. The research wascarried out in the Tissue Culture Laboratory, agriculture’s Faculty of North Sumatera University from Juneto September 2013. This research used Randomized Block design with two factors. First factor was sucroseconcentration consist of four level: 35 g/l; 50 g/l; 65 g/l; 80 g/l. The second factor was 2-ip concentrationconsist of five level are 0 mg/l; 2 mg/l; 4 mg/l; 6 mg/l; 8 mg/l. The results showed that sucrose gavesignifiantly effect to number of nodes after darkness period parameter. 2-ip concentration give significantlyeffect only on number of nodes after lighting period. Interaction of sucrose and 2-ip have no effectsignificantly to all parameterKeywords : Sucrose, 2-Isopenteniladenine (2-ip), Potato Nodes, In Vitro